THE USE OF BAMBOO AS THE ARTWORK MEDIA FOR THE STUDENTS AT SENIOR HIGH SCHOOL - Tirza Paula Pantow; Ruly Rantung; Jans G. Mangare (SoCul: International Journal of Research in Social Cultural Issues, 2023)
One aspect that is considered a sign of a school's progress is its ability to adapt to technological developments. SMA Negeri 1 Kumelembuai is an example of a school that has successfully adapted to technological developments. Even though adequate technological learning facilities are available, it is not certain that students can become creative individuals without the guidance of teachers who also have high creativity. This has proven important in developing students' potential through creative and innovative learning approaches. The present study aims at describing the the fine arts learning at SMA Negeri 1 Kumelembuai where the the students used bamboo as the artwork media. This research amployed a qualitative approach as a research method. The reason for choosing a qualitative approach is because this approach allows researchers and research subjects to interact during the research process, which allows changes and development of the research design. The results of this research show that the use of bamboo waste as a medium for creating art by class X at SMA Negeri 1 Kumelembuai is a new innovation, with the potential to produce works of art that can be developed into a home industry.